Valuable compounds in coffee by-products - Esquivel Rodríguez, Patricia (2019)
Coffee is extensively consumed as one of the most popular beverages, but at the same time it is a major source of organic residues. When not adequately disposed or processed, these residues are a cause of environmental and health concerns. Beneficial properties have been attributed to coffee, not only due to its caffeine contents, but also due to the presence of valuable compounds such as chlorogenic acids. The role of coffee as a beverage in prevention of diseases has been widely discussed. Among other reasons, increasing interest in coffee by-products has been ascribed to their potential as functional ingredients for food, pharmaceutical, and cosmetic industries. Pointing out to the industrial uses, it is important to consider that coffee pulp, which results from the coffee berry processing, comprises almost 45% of the cherry, being a valuable material for several purposes. Major polyphenols described in coffee pulp are flavan-3-ols (monomers and procyanidins), hydroxycinnamic acids, flavonols, and anthocyanidins. Moreover, additional by-products of coffee processing, such as the mucilage and the fiber fractions, parchment, and silverskin, have also been studied. The aim of this chapter is to review recent information related to the utilization of coffee processing by-products, focusing mainly on the health beneficial properties, but also on other uses when appropriate.